GAME EDUKASI PENGENALAN HURUF DAN ANGKA USIA DINI: Education;Early Childhood;Child Growth;Games. - Nilawati; Riswan; Yeniwati, Desy; Rafindo (LP2M Universitas Nurdin Hamzah, 2022)
Educational games as additional media in the process of learning and teaching early childhood in Harapan Bunda Kindergarten, Mestong District, Muaro Jambi Regency. Where in this kindergarten there is no available learning media in the form of educational games. The results of this research are expected to be used as additional references in early childhood learning. To create a quality generation, education must be carried out from an early age in this case through Early Childhood Education. This game is designed with educational elements and attractive designs for children with the aim of fostering learning motivation with simulation media in the form of games.